On some tropical hydroids (Cnidaria: Hydrozoa), with descriptions of four new species - Galea, Horia R.; Maggioni, Davide (Zootaxa, 2024)
The present study provides a morphological account of six tropical hydroids, of which four are described as new. Halecium turbinariae sp. nov. grows exclusively on brown algae of the genus Turbinaria (Phaeophyceae: Fucales), and contains numerous zooxanthellae in its coenosarc. Nemalecium caeruleus sp. nov. occurs in a peculiar ecological niche, viz. the crevices of scleractinian corals, and is distinguished from its congeners by its sympodial mode of branching and an original, bluish-fluorescent sheen of its polyps. Antennella flava sp. nov. belongs to the A. secundaria (Gmelin, 1791) species group, but its tissues are abundantly filled with zooxanthellae, conferring it a striking yellow coloration. Macrorhynchia fallax sp. nov. imitates the fine morphology of M. philippina Kirchenpauer, 1872, although live specimens lack the characteristic irisation of the cladia met with in the latter. The peculiar, decapod crab-associated Corymorpha balssi Stechow, 1932, so far only known from the original account, is rediscovered and redescribed based on its hydroid stage and the ready-to-detach medusae. According to the morphological features of the latter, C. bitungensis (Xu, Huang & Guo, 2013), and possibly C. juliephillipsi (Gershwin et al., 2010), are considered the mature medusa stages of the same species, and are regarded as potential junior synonyms. The controversial synonymy of Tridentata borneensis (Billard, 1925) is addressed based on the examination of new material and its comparison with part of the type series, supplemented by the reinspection of the types of several nominal species subjectively assigned earlier to its synonymy. The distinctive sculpture of the hydrothecal wall leaves little doubt that it has a recent junior synonym, viz. Sertularia vervoorti Migotto & Calder, 1998, syn. nov. Conversely, the following taxa are removed from its synonymy upon the reevaluation of their taxonomic statuses: 1) Thuiaria maldivensis Borradaile, 1905 is a valid species that has a junior synonym, namely Pasythea heterodonta Jarvis, 1922 (now Dynamena), syn. nov., the former being henceforth referred to as Dynamena maldivensis (Borradaile, 1905), comb. nov., on the account of its polyps lacking an abcauline caecum; 2) Tridentata westindica Stechow, 1919, syn. nov., is a junior synonym of Tridentata turbinata (Lamouroux, 1816); 3) Sertularia tongensis Stechow, 1919 is a valid species that has a recent junior synonym, viz. Sertularia orthogonalis Gibbons & Ryland (1989), syn. nov.; 4) Sertularia tumida Allman, 1877, whose type is reportedly lost, is removed from the synonymy of Billard’s (1925a) species, on the account on its much longer internodes; 5) Sertularia malayensis var. sorongensis Leloup, 1930 remains a subjective junior synonym; 6) also reexamined was type material of the little-known, not formerly illustrated Tridentata occulta Stechow, 1926, syn. nov. of Amphisbetia distans (Lamouroux, 1816). Additionally, we provide single- (16S rRNA or COI) and multi-locus (16S, 18S and 28S rRNA) phylogenetic analyses for many families of athecate and thecate hydroids, including at least 57 species from Bali, with 25 nominal species characterized genetically for the first time. Halecium halecinum var. minor Pictet, 1893 is raised to species, as H. minor Pictet, 1893, nov. status, on both morphological and molecular grounds. Campanularia spinulosa Bale, 1888 is assigned to the genus Obelia Péron & Lesueur, 1810, as O. spinulosa (Bale, 1888), based on its genetic affinities.